Menemukan Konsep Basilea dalam Lagu Tupac Shakur Ghetto Gospel: Suatu Kajian Teologi dan Budaya Populer - Mofun, Costantinus Ponsius Yogie (Theologia in Loco, 2024)
Theology and popular culture are two things that are very important to see in today’s context. Many people are beginning to see popular culture as part of their lives and cannot be let go. This can be seen in music, which is not only popular culture but also part of the culture itself. There are many forms of understanding of music, both negative and positive. Hip-hop music is by far a trending music in the context of the younger generation. One of the users of this music is Tupac Amaru Shakur. He is both a legend and an icon of hip-hop music. His songs are still heard today and have become favorites in various circles. This is because his songs hold a variety of theological meanings and values that are quite deep; therefore, this article will examine the theological meaning and value of one of his songs, Ghetto Gospel.